2009
DOI: 10.1177/0969733009342636
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Organizational Climate: Nurses’ Insights Into Their Relationship With Physicians

Abstract: Within any organization (e.g. a hospital or clinic) the perception of the way things operate may vary dramatically as a function of one's location in the organizational hierarchy as well as one's professional discipline. Interorganizational variability depends on organizational coherence, safety, and stability. In this four-nation (Canada, Ireland, Australia, and Korea) qualitative study of 42 nurses, we explored their perception of how ethical decisions are made, the nurses' hospital role, and the extent to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 60 publications
2
75
0
Order By: Relevance
“…At the organizational level, the supportive environment for ethical decision‐making was emphasized (Lützén & Schreiber , Malloy et al . , McGrath & Phillips ). Collaboration and communication (Åström et al .…”
Section: Resultsmentioning
confidence: 98%
“…At the organizational level, the supportive environment for ethical decision‐making was emphasized (Lützén & Schreiber , Malloy et al . , McGrath & Phillips ). Collaboration and communication (Åström et al .…”
Section: Resultsmentioning
confidence: 98%
“…From nurses' point of view, some of the most painful practical tensions arise because they lack the authority to act on their own, to exercise their own judgment, to take the initiative and to go against physicians' orders ( Thompson et al 2006). An international study demonstrated similar findings: "Nurses felt that they lacked either power to speak against physicians' opinions", or "[n]urses believed that their opinions would not be accepted" (Malloy et al 2009). …”
Section: Can Care Responsibility Play Out Within Trustrelationships Wmentioning
confidence: 83%
“…[16] In nurses’ view, as reported in Simpson, a good physician is one who respects what a nurse does, who asks for nurses’ opinions, and trusts their judgement. [17] Interestigly, Schmalenberg describes nurse–physician relationships as a teacher–student relationships where both parties can simultaneously act as ateacher and benefit from the other party's opinions and experience.…”
Section: Discussionmentioning
confidence: 99%